Diagnostic action against hypertransaminasemia in paediatrics: Consensus document of Sociedad Española de Gastroenterología, Hepatología y Nutrición Pediátrica (SEGHNP), Asociación Española de Pediatría de Atención Primaria (AEPap) and Sociedad Española de Pediatría de Atención Primaria (SEPEAP) - Ignacio Ros Arnal; Joaquín Reyes Andrade; María Mercadal Hally; Luis Carlos Blesa Baviera; Diana García Tirado; Samuel Héctor Campuzano Martín; Estela de la Calle Navarro; Ana María Vegas Álvarez (Elsevier, 2022)
Hypertransaminasemia is a frequent finding in pediatrics, which could reflect potentially treatable serious disease. The aim of this document is to establish, by reviewing the available evidence, a consensus for an adequate management of hypertransaminasemia, from its detection until the study is complete. To this end, a working group was formed with the participation of members of the Society of Pediatric Gastroenterology, Hepatology and Nutrition (SEGHNP), the Spanish Association of Primary Care Pediatrics (AEPap) and the Spanish Society of Primary Care Pediatrics (SEPEAP). Twenty-one recommendations are established with a marked practical component that will be useful in hospital clinical practice and primary care. Resumen: La hipertransaminasemia es un hallazgo frecuente en pediatría, puede ser banal o reflejar enfermedad grave potencialmente tratable. El objetivo de este documento es establecer, mediante la revisión de la evidencia disponible, un consenso para un adecuado enfoque práctico desde la detección de la hipertransaminasemia hasta completar su estudio en la edad pediátrica. Para ello, se constituyó un grupo de trabajo con participación de miembros de la Sociedad de Gastroenterología, Hepatología y Nutrición Pediátrica (SEGHNP), Asociación Española de Pediatría de Atención Primaria (AEPap) y Sociedad Española de Pediatría de Atención Primaria (SEPEAP). Se establecieron 21 recomendaciones con el objetivo de que sirvan de utilidad en la práctica clínica habitual tanto en atención primaria como hospitalaria.